Die Klimaklassifikation von Budyko und Grigor´ev - Giese, Ernst (ERDKUNDE, 1996)
As in the USA there has developed in the USSR in recent times, too, a theoretical physical climatology. This development has been promoted particularly by the research of Budyko and Grigor’ev on the heat and moisture balance of the earth’s surface, Based on this research Budyko and Grigor’ev have developed a classification of climate, which is remarkable for its exact physically based of deliniation and the use of a new and complex deliniation parameter, the so called radiation index of dryness. According to this classification Budyko and Grigor’ev have defined the climates of the USSR and constructed a map of the climatic regionalization of the USSR.